2011
DOI: 10.1093/cvr/cvr014
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone is a DPP-IV inhibitor and increases SDF-1-driven homing of CXCR4+ stem cells into the ischaemic heart

Abstract: In summary, PTH is a DPP-IV inhibitor leading to an increased cardiac SDF-1 level, which enhances recruitment of CXCR4(+) BMCs into the ischaemic heart associated with attenuated ischaemic cardiomyopathy. Since PTH is already clinically used our findings may have direct impact on the initiation of studies in patients with ischaemic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 44 publications
(53 reference statements)
1
42
0
Order By: Relevance
“…60 -64 A single PTH injection significantly increased SDF-1 mRNA in the marrow of wild-type but not mutant mice, which may explain the blunted increase in marrow SDF-1 protein levels in PTH-treated Prg4 mutant mice. In the light of recent work demonstrating that intermittent PTH administration inhibits dipeptidyl peptidase-IV (DPP-IV), 65 an enzyme that functionally degrades SDF-1, an alternative explanation for the blunted PTH increase in marrow SDF-1 is that PTH actions protecting marrow SDF-1 from enzymatic degradation are decreased in Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…60 -64 A single PTH injection significantly increased SDF-1 mRNA in the marrow of wild-type but not mutant mice, which may explain the blunted increase in marrow SDF-1 protein levels in PTH-treated Prg4 mutant mice. In the light of recent work demonstrating that intermittent PTH administration inhibits dipeptidyl peptidase-IV (DPP-IV), 65 an enzyme that functionally degrades SDF-1, an alternative explanation for the blunted PTH increase in marrow SDF-1 is that PTH actions protecting marrow SDF-1 from enzymatic degradation are decreased in Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PTH, which does not have a truncation site, is a negative regulator of DPP4 and allows for stem-cell mobilization from the bone marrow to sites of ischemic injury. 70 Proteins such as CXCL12, OPN, EPO, IL-6, and IL-3, which are important in niche regulation potentially via PTH, have putative DPP4 truncation sites (Tables 1-3), whereas others (Notch-1, Jagged-1, IL-7) do not. Thus, some of the factors regulating the niche may be acting via their truncated, not full-length, forms.…”
mentioning
confidence: 99%
“…Similarly, Huber et al showed that systemic rhPTH induced an SDF-1 homing gradient to the ischemic myocardium, attracting bone marrow-derived stem cells and, in effect, improving myocardial function after infarction in a murine model. 31 In the current study, we show that endogenously mobilizing stem cells and concomitantly enhancing their trafficking yield a remarkable increase in bony healing. Whereas systemic AMD3100 administration resulted in 59.7% bony ingrowth and PTH alone resulted in 56% bony ingrowth, together, a synergistic effect of 90.6% bony regeneration was achieved; this was associated with significantly increased numbers of cPCs and CD31 staining in the trephine defect.…”
Section: Discussionmentioning
confidence: 51%
“…Although rhPTH has long been known to improve osteoblastic bone-forming parameters, there is some evidence to suggest that it may also act to enhance stem cell trafficking to sites of injury. [10][11][12]30,31 For example, Zaruba et al 12 and Huber et al 10 showed that systemic Teraparatide administration enhanced the homing of BM cells to the ischemic myocardium and reduced infarction size in mice. The authors postulated that the Teraparatide was acting by increasing the numbers of CD45 + /CD34 + cells trafficking to the myocardium, which resulted in increased vascular endothelial growth factor messenger RNA expression, increased neovascularization, and increased myocardial survival.…”
Section: Discussionmentioning
confidence: 99%